Optimalisasi Pengelolaan Situs Jurnal Fakultas Ilmu Sosial dan Ilmu Politik UIN Sunan Ampel Surabaya: Melalui Webinar Pelatihan bagi Pengelola Jurnal - Hidayatullah, Nur Luthfi (Universitas Islam Negeri Sunan Ampel, 2024)
This action research seeks to train journal managers from the Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya to design the journal website’s layouts through a training webinar. The journal website’s layout becomes the main criteria to apply for journal accreditation. This action research utilizes Participatory Action Research method, which includes problem formulation, planning, and reflecting upon social changes that happened. This action research was conducted for a month, with lecturers in charge of managing seven journal websites of FISIP UINSA as the participants. The results of this action research prove that there are seven stages that need to be done in optimizing journal site management, including consultation with supervisors with the output of revised action research designs; socialization to journal site managers resulting in good journal site criteria; submitting proposals to training webinar speakers; organizing a Journal Site Management Training Webinar with video recording; implementing the results of the webinar by improving the appearance of the journal site; socializing the improved journal site through tutorial video and survey; and designing a roadmap to apply for journal accreditation.